PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN KARAKTER PESERTA DIDIK - Sumarno, Sumarno (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2016)
Islamic education is one of the subjects which aims at building the moral of student. Moral is one major foundation in building of human culture. Character education is motived by declining of moral issues. Islamic education teacher has an important role in character building of student by implementing its role as mentors, role models, advisors, and evaluators. the efforts that are done by teacher in character building of student by means of : (a) giving the example of the student (b) controlling and mentoring with a religious. (c) commiting habit such as praying dhuha and dzuhur in congregation and reading qur'an (d) giving reward and punishment (e) constructing student discipline (f) holding the cooperating with the parent of the student. Â Keywords : teacher, character building, student